Соғлом турмуш тарзини талабалар онгига сингдириш орқали касбга тайёрлаш йўллари - nurmatov, eldor (Физическое воспитание, спорт и здоровье, 2022)
Health to life is organisational it is in the way causes mechanizm ar deep learning, developing it is person healthy is taken into confederation living necessity level is developing important, sulmination problem because will appeal to the past century a verious peoples representative this is problem what considerable very important. Certanly health to life is taken shape problem about a verious direction scientist is searching yet.